Bacterial Community Dynamics during Bioremediation of Diesel Oil-Contaminated Antarctic Soil - Vázquez, Susana Claudia; Nogales, Balbina; Ruberto, Lucas Adolfo Mauro; Hernández, Edgardo; Christie Oleza, Joseph; Lo Balbo, Alfredo; Bosch, Rafael; Lalucat, Jorge; Mac Cormack, Walter Patricio (Microbial Ecology)
The effect of nutrient and inocula amendment in a bioremediation field trial using a nutrient-poor Antarctic soil chronically contaminated with hydrocarbons was tested. The analysis of the effects that the treatments caused in bacterial numbers and hydrocarbon removal was combined with the elucidation of the changes occurring on the bacterial community, by 16S rDNA-based terminal restriction fragment length polymorphism (T-RFLP) typing, and the detection of some of the genes involved in the catabolism of hydrocarbons. All treatments caused a significant increase in the number of bacteria able to grow on hydrocarbons and a significant decrease in the soil hydrocarbon content, as compared to the control. However, there were no significant differences between treatments. Comparison of the soil T-RFLP profiles indicated that there were changes in the structure and composition of bacterial communities during the bioremediation trial, although the communities in treated plots were highly similar irrespective of the treatment applied, and they had a similar temporal dynamics. These results showed that nutrient addition was the main factor contributing to the outcome of the bioremediation experiment. This was supported by the lack of evidence of the establishment of inoculated consortia in soils, since their characteristic electrophoretic peaks were only detectable in soil profiles at the beginning of the experiment. Genetic potential for naphthalene degradation, evidenced by detection of nahAc gene, was observed in all soil plots including the control. In treated plots, an increase in the detection of catechol degradation genes (nahH and catA) and in a key gene of denitrification (nosZ) was observed as well. These results indicate that treatments favored the degradation of aromatic hydrocarbons and probably stimulated denitrification, at least transiently. This mesocosm study shows that recovery of chronically contaminated Antarctic soils can be successfully accelerated using biostimulation with nutrients, and that ...